Mysterious dengue‐like virus: A case report from Pakistan. Issue 7 (18th July 2022) - Waseem, Summaiyya; Ahmed, Syed Hassan; Shaikh, Taha Gul; Qadar, Laila Tul; Khalid, Saad; Nimavat, Nirav; Hasan, Mohammad Mehedi
Abstract: Recently, in Pakistan, several cases of mysterious dengue‐like illness are being reported, which has concerned the authorities and requires prompt action. We present a case of a 52‐year‐old female patient presenting with a history of continuous fever, documented up to 104 F, for 5 days. The symptoms were associated with headache, nausea, retro‐orbital headache, arthralgia, and myalgia. Currently, to the best of our knowledge, this is the first reported case in the literature for the endemic mysterious virus and may serve as the groundwork for future studies. Abstract : The mysterious virus, presenting with symptoms similar to dengue, is currently presumed to be endemic in Pakistan. The classical presentation of the viral fever is headache, nausea, retro‐orbital headache, arthralgia, myalgia, and fatigue. Till now, no known mortality has been reported under the pounce of this virus.